De novo assembly of a wild swan goose (Anser cygnoides) genome. (9th September 2022) - Zhang, Yonghong; Ni, Hongyu; Xie, Hengli; Yin, Yijing; Zheng, Jinlei; Dong, Liping; Diao, Jizhe; Yan, Shouqing; Yang, Yuwei; Sun, Hao; Sun, Xueqi
Abstract: The swan goose ( Anser cygnoides ) is the ancestor of the Chinese domestic goose. A previous study reported a scaffold‐level genome version for a Chinese indigenous goose breed, and this assembly was used as the swan goose's reference genome. To date, there is still a lack of a chromosome‐level genome for the swan goose . Here, we reported a de novo assembly of the genome of a wild swan goose using an integrated strategy that combines Illumina Hiseq, Oxford Nanopore and chromosome conformation capture (Hi‐C) sequencing. A total of 134.6 Gb Nanopore data with sequencing coverage of 110.33 and 69.45 Gb Illumina data with coverage of 56.93 were obtained. The genome assembly size was 1153.41 Mb, with a contig N50 of 22.75 Mb. The total size and N50 length of our assembly were larger than the previously reported scaffold‐level genome version. In addition, whole‐genome sequencing data of 10 geese were mapped to the previous and the current assemblies. On average, 97.88 and 93.18% of the reads were properly mapped and paired into our and the previous assemblies. This high‐quality chromosome‐level swan goose genome could provide a valuable resource for the utilisation of goose studies and breeding.